Prevalence and trends of autism spectrum disorder and other developmental disabilities among children and adolescents in the United States from 2019 to 2021 - Ge, Wenrong; Zhang, Cancan; Yang, Guang; Zhang, Bo (Frontiers in Psychiatry, 2024)
The National Health Interview Survey (NHIS) is a comprehensive health survey conducted by the National Center for Health Statistics (NCHS) in the U.S., providing valuable insights into the health status of the population. This study focuses on the NHIS child survey between 2019 and 2021, exploring developmental disabilities in U.S. children, including autism spectrum disorder (ASD), attention deficit/hyperactivity disorder or attention-deficit disorder (ADHD/ADD), intellectual disability (ID), other developmental delay (other DD), and learning disability (LD).Objective: Leveraging NHIS data, our primary objective is to investigate the latest trends and disparities in the prevalence of developmental disabilities among various racial-ethnic groups.Methods: Employing a repeated cross-sectional design, we analyzed NHIS data from 2019 to 2021, focusing on children aged 3-17. The survey employed a meticulous stratified multi-stage sampling design. We utilized SAS version 9.4 for data analysis, calculating race-ethnicity-specific prevalence rates and employing weighted linear regression and the Rao-Scott chi-square test for trend analysis.Results: Among 19,490 children, prevalence rates varied: ASD (3.11%), ADHD/ADD (9.50%), ID (1.85%), other DD (5.66%), and LD (7.49%). Non-Hispanic black children exhibited higher rates of ID and LD, while non-Hispanic white children had the highest ADHD/ADD prevalence. Disparities persisted across sociodemographic subgroups, with variations in prevalence rates.Our study reveals an increase in ASD prevalence and persistent disparities among racial-ethnic groups.Non-Hispanic black children face elevated risks of ID and LD, while non-Hispanic white children exhibit higher rates of ADHD/ADD.